Global meaning making : disrupting and interrogating international language and literacy research and teaching - Assaf, Lori Czop; Sowa, Patience Adjekai; Zammit, Katina (Advances in research on teaching, 2022)
We live in an increasingly interdependent and interconnected world. The COVID-19 crisis has provided a stark reminder of the enormous educational inequities within and across countries around the globe. Featuring international language and literacy researchers who apply various tenets of global meaning making to disrupt and interrogate contradictions and tensions in global scholarship, Global Meaning Making focuses on a model of interrogating international literacy research and pedagogical pursuits with the ultimate goal of transforming how we engage in global endeavours. Organized around three major themes: Literacy Programs, Policies and Curriculum; Language of Instruction Policies and Practices and Engaging in Global Literacies, chapter authors reimagine global approaches that respect the histories, ways of knowing, needs, hopes and values of voices beyond the western, including those from the Global South: Asia, Africa, Oceania, and South and Central Americas. Each chapter outlines research the chapter authors are conducting or have conducted and describes implications for how their work utilizes tenets of global meaning making.